Awareness of risk factors for coronary heart disease following interventional cardiology procedures: a key concern for nursing practice - Fernandez, R.; Salamonson, Y.; Griffiths, R.; Juergens, C.; Davidson, Patricia (Blackwell Publishing, 2008)
Cardiovascular risk factor modification to prevent progression of coronary heart disease is important for patients following percutaneous coronary intervention. The aims of this study were to assess patient's awareness of modifiable cardiac risk factors and examine if patients with modifiable risk factors were more likely to identify these risk as amenable to change. Awareness of risk factors was measured using the Indiana Cardiac Rehabilitation Knowledge Questionnaire in a cohort of prospective, consecutive participants post percutaneous coronary intervention. Completed questionnaires were received from 75% of the participants. The majority were able to identify high cholesterol (87%), smoking (83%) and hypertension (82%) as modifiable risk factors. Less than half (46%) of the respondents identified diabetes as a modifiable risk factor. Only a third of participants recognized all six modifiable risk factors. A large proportion of patients who were smokers, or who had high cholesterol or hypertension, identified these as risk factors. A third of people with documented diabetes did not recognize this condition as a risk factor for heart disease. The findings have important implications for nursing practice in terms of directing educational efforts for the modification of risk factors for coronary heart disease.